Nursing Satisfaction with Medication Care by Using Neonatal Electronic Medication Management Systems - Mahboobeh Namnabati; Fariba Taleghani; maryam varzeshnejad (Mashhad University of Medical Sciences, 2017)
Background: Medication management is a complex process with multiple stages that involves different health care teams. Based on the evidence, an electronic medication management system offers significant benefits, such as reduced medication errors, improved conformity, enhanced time and cost efficiency, and increased patient safety. This study aimed to design and implement an electronic medication management system and measure the nurse's satisfaction regarding the application of this system. Methods: In this technical action research, the nurses' satisfaction with the use of the designed system was evaluated. The electronic medication system development and data collection were conducted in two phases. The first phase included the design and development of an electronic nursing medication management system to be used in the neonatal intensive care unit. The second phase involved the evaluation of the nurses' satisfaction with the use of the electronic system by applying a five-point Likert scale questionnaire. Results: The findings were divided into two categories, including results related to the design of the electronic systems and those regarding the evaluation of nurses' satisfaction with the use of the electronic systems. The design of the electronic system was successful as the nurse's satisfaction evaluation revealed a high level of satisfaction with the use of the system. Conclusion: Electronic medication management system has more practical advantages than other similar systems. This system helps the nurses to identify and prevent many medication errors and save time in drug care documentation. Therefore, this system is a big step towards satisfaction with nursing medication care.